Audit Committee Characteristics and Financial Reporting Quality: Evidence from Nigerian Listed Companies - Madakawi, Abdulkadir (2012)
This research examines whether the formation of audit committees and its characteristics are associated with improved financial reporting quality. The sample of the study is the Nigerian listed companies prior to and after the introduction of mandatory audit committee requirements in The Code of Corporate Governance in 2003. The researcher uses an archival data from the annual reports, NSE and SBAInteractive. The model by Dechew and Dichev (2002) was used to measure the earnings quality as proxy for financial reporting quality. The result indicates that there was some evidence that earnings quality significantly reduced in the years after audit committee formation, thus providing some support for the notion that the formation of the audit committee improved financial reporting quality. Second finding shows that there was a weak association between the characteristics of audit committee and improved financial reporting quality. The audit committee independence and expertise are found to significantly associate with improved financial reporting quality. Audit committee meets 4 to 5 times a year and audit committee size consists of 4 members. The result also shows that 70% of the sample firms employed Non-Big 4 auditors. These findings provide evidence on the mandatory audit committee requirement under the NSE listing rules on how the companies respond towards The Code.